Relying on the views and opinions of librarians to know the reality of the level of electronic information services provided in school libraries in the province of Karak - Abu Samhadana, Emad Ahmed (Journal of Humanities & Social Sciences, 2021)
This study focused on the view and opinion of school librarians about the extent of electronic information services provided in school libraries in the Hashemite Kingdom of Jordan. And studied this problem: through the provision of school libraries' electronic information services; what level of their ability to help the success and improve the teaching process.The views and opinions of librarians were collected through a questionnaire on the reality of electronic information services provided by school libraries of the Ministry of Education in the Hashemite Kingdom of Jordan. The study included librarians in public schools in the academic year 2016-2017. The study focused on school librarians, whether male or female, in the general public education community in Karak governorate. The researcher used the descriptive, analytical approach and the opinions of the librarians in the information services. To collect the data, the researcher used a questionnaire to know the situation of officials and staff of information services in school libraries and also to identify the problems facing these services and to know future plans to improve and develop information services provided in school libraries.Due to the lack of Internet, the lack of integrated automated systems, the lack of computers for employees or beneficiaries, the lack of marketing activities, the lack of exploitation of social networks, and the lack of cooperation between school libraries in the field of information services in Jordan; Most libraries offer traditional services such as reference service, secondment, etc., as indicated in this study. Electronic information services in school libraries face many difficulties or challenges or important problems, such as lack of information network, budget, the provision of computers rarely, the lack of training programs, and therefore this achieves the desired objectives for libraries negatively affected by these difficulties and challenges.The study focused on a set of hypotheses and the results were as follows: For the response of the sample on the difficulties facing electronic information services, there are differences with statistical function, due to a set of variables such as (gender, participation in training courses), but because of these two variables (knowledge of tasks There are no statistically significant differences.
Keywords: Information and Communication Technology (ICT); Librarians; Electronic Information Services; School Libraries